What does knowledge work do? - Ray, Tim (Henry Stewart Talks, 2011)
Peter Drucker, Knowledge workers, Abstract nouns, Transitive verbs, War on Terror, Frederick Winslow Taylor, Scientific Management, Reductionism, Ikujiro Nonaka, Knowledge Management, Michael Polanyi, Truth, God, Tacit knowledge, Explicit knowledge, Paul Watzlawick, Communication, Intersubjective, Japanese management, Ernst von Glasersfeld, Radical constructivism, Trust, Practice, Doing, Moral responsibility